Educational Technologies for Teaching Social Skills to Individuals With Schizophrenia: Scoping Review. (January 2023) - Surdyka, Nicole; Clark, Amy; Duncan, Andrea
Schizophrenia interventions incorporate improving quality of life and social functioning. Educational technologies are a potential treatment method for social skills development among individuals with schizophrenia. The objective of the study is to provide an overview of the characteristics and range of approaches of educational technologies in the context of social skills for individuals with schizophrenia. A scoping review methodological framework was applied. Search strategy was conducted on Ovid MEDLINE® and CINAHL Plus. Data were synthesized using a charting form for a logical, descriptive summary of results. The search yielded 771 results and 23 included studies that met eligibility criteria. The data showed persons with schizophrenia respond well to educational technologies to address illness self-management. Using technology in conjunction with traditional evidence-based interventions demonstrates promising results to improve social skills functioning. Occupational therapists can use educational technologies to decrease the gap in health care services and improve social support for individuals with schizophrenia.